REVOLUSI ILMU PENGETAHUAN DAN RELEVANSINYA TERHADAP PEMBAHARUAN HUKUM ISLAM - Mustaring, Mustaring (DIKTUM: Jurnal Syariah dan Hukum, 2014)
The development of Thomas Kuhn's epistemology has brought certain changes in human civilization and a major influence on thinkers of Islam. Kuhn has interesting fact that the philosophers of science generally ignores the basic hermeneutic issues such as the question of what is actually done by a scientist. According to Kuhn rasioanalitas ambiguous scientific fact that basically is not merely a matter of induction or deduction or rasioanalitas also objective, but rather on matters of interpretation (hermeneutical) and persuasion which tends to be more subjective. Methods renewal of Islamic law and family law in contemporary Islamic thought though shades of change is quite pronounced but reform law paradigm of classical legal methodology to a new methodology be applied is still rare. Because according to legal experts who are still using the classic paradigm of new methods offered does not offer a complete solution in addition to the still strong around the confines of dogmatic result of this apathy is getting stronger, and most of the Islamic State and non- state wear Islamic law and Islamic law most families in particular are still patterned utilitarianistik. But stretching renewal undertaken by thinkers over a bit much to excite a new study in the field of family law in particular and Islamic thought in general and also become a point of departure expectations change when Muslims slumped amid the swift currents of change .